Challenges and opportunities for Australian osteopathy: A qualitative study of the perceptions of registered osteopaths. (December 2018) - Blaich, R.; Steel, A.; Clark, D.; Adams, J.
Abstract: Background: The professional landscape of osteopathy in Australia has evolved substantially over recent years including changes in research, education and integration within the wider healthcare system. The challenges and opportunities experienced by members of the Australian osteopathic profession warrant closer examination. Objective: Explore the perceptions of registered practising osteopaths in Australia regarding challenges and opportunities for the profession. Design and setting: The study employed a qualitative inductive design and approach through which three focus groups of registered practicing osteopaths were convened across three Australian locations. Methods: The data were collected through semi-structured thematic guides. Data were analysed from transcripts using framework analysis. Participants: Registered osteopaths (n = 17) participated in the focus group representing a range of gender, age, education, and years of practice amongst participants. Results: Thematic descriptive analysis of the osteopaths' accounts identified different perspectives about whether the osteopathic profession was moving in the optimal direction. These included a question about whether osteopaths were best placed as generalists or specialists; the importance of quality education and relevant, rigorous research as pillars for the sustainability of osteopathy; a need for clarity about the place of osteopathy in the healthcare system; and the need to increase public awareness about osteopathy. Conclusion: This study highlights a number of these challenges and in doing so, provides an opportunity for stakeholders to find appropriate solutions to support the advancement of the profession. To this end there needs to be more effective communication/liaison between the osteopathic profession and education providers, regulators, Government departments, and other healthcare professionals. Highlights: There are different perspectives among osteopaths regarding the perceived value of generalist and specialist osteopathic practice. Quality research and education are viewed as pillars to the ongoing sustainability of the osteopathic profession. Osteopaths are challenged by a lack of clarity regarding their place in contemporary healthcare. Increased public awareness of osteopathy may improve the viability of osteopathic practice.